Género y nivel educativo en las narrativas autobiográficas de la infancia - Marcia Leticia Ruíz Cansino; Ma. Del Rosario Contreras Villarreal; Luis Humberto Garza Vázquez (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2012)
The present work deals with autobiographic memory, educative background and gender roles. It is based in socio–cultural psychology research supporting the relationship between context and the development of cognitive processes. 96 structured interviews were made in Cd. Victoria, Tamaulipas to men and women with different educative background: literacy, basic education and university, they ranged between 30 and 55 years old. Personal recollections analysis is based in the categories proposed by Wang (Wang 2001, Wang y Conway 2004). Roles of main characters present in the autobiographical narratives were also investigated using family, educational, work, recreational, and sport contexts. The results shows that women childhood narratives centered in social themes, it has more emotional expresions and the roles are related to child care, domestic work and the enjoyment of school work. Men narratives content is about their own wishes and interests, it has less emotional verbal expressions, they are prone to help with child care but not with domestic work, besides, they show a bigger interest in sports. It was also found that the greater the educative background, the larger the narrative production.